Design of woven meta-materials for electronic textiles for functional applications. Issue 5 (4th May 2023) - Zribi, Hanen; Taieb, Amine Hadj; Gil, Ignacio; Fernández-García, Raúl; Ardanuy, Mònica
Abstract: In this paper, woven wearable metamaterials are developed. For this purpose, several frequency selective surface (FSS) textile absorbers are proposed. The main structure of the FSS consists of a fabric with different patch shapes, a back ground plate (conductive layer) and a textile substrate. Firstly, the effect of the substrate used on the S-parameters and absorbance in order to detect the best substrate is analyzed. Then, once selected the best substrate, the effect of the patches' shape on the performance of the wearable metamaterial is analyzed. It was found that the fabric that gives the best results is the one composed of 65% polyester and 35% cotton and the best patches are the cross-shaped ones. The developed FSS can be used in wearable textiles to protect the human body from microwave radiation emissions.